Layered manganese-based metal–organic framework as a high capacity electrode material for supercapacitors. Issue 47 (7th June 2017) - Wang, Xianmei; Liu, Xiuxiu; Rong, Hongren; Song, Yidan; Wen, Hao; Liu, Qi
Abstract : The layered Mn-based metal–organic framework (Mn-LMOF) displayed good performance as an electrode material for supercapacitors. Abstract : For the development of supercapacitors with higher energy densities, metal–organic frameworks (MOFs), as electrode materials for supercapacitors, have attracted much attention. Herein, layered manganese-based MOF ([Mn(tfbdc)(4, 4′-bpy)(H2 O)2 ], Mn-LMOF; H2 tfbdc = 2, 3, 5, 6-tetrafluoroterephthalic acid, 4, 4′-bpy = 4, 4′-bipyridine) was synthesized by a simple solution reaction and evaluated as an electrode material for supercapacitors for the first time. The Mn-LMOF electrode showed a high specific capacitance, a good cycling stability and a improved rate capability. Its maximum specific capacitances were 1098 F g −1 for 1 M KOH and 1178 F g −1 for 1 M LiOH solutions at a current density of 1 A g −1 . The specific capacitance retention was maintained at 92.6% after 2000 cycles in 1 M KOH, slightly lower than that in 1 M LiOH. The excellent supercapacitive performance may be ascribed to the nature of Mn-LMOF, containing a layered structure and nano-sized particles.